Membangun Perekonomian di Desa Penaga Melalui Pengolahan Ikan Menjadi Kerupuk Ikan - Tubel Agusven; Risnawati Risnawati; Selvi Fauzar; Rapida Nuriana; Satriadi Satriadi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Each village has potential, both physical potentials such as climate, soil, water, geographical environment, human resources and others as well as non-physical potentials such as community culture. In Penaga Village, Teluk Bintan District, the majority of people's livelihoods as fishermen and marine catches are still not optimally utilized. Therefore, service activities to process fish into fish crackers to support the economy of the people of Penaga Village as one of the efforts to empower the community towards independence in entrepreneurship and optimize the utilization of potential. The service method is carried out with a training program where this program is one part of the community service program activities in the form of training on how to process fish crackers by utilizing marine catches into fish crackers so that they can have more selling value, business licensing and legality, and marketing through digital marketing. It is hoped that after attending this training, the community will be motivated to develop the potential in Penaga Village